The GAGA factor is required in the early Drosophila embryo not only for transcriptional regulation but also for nuclear division. - Bhat, K.M.; Farkas, G.; Karch, F.; Gyurkovics, H.; Gausz, J.; Schedl, P. (Development, 1996)
The GAGA protein of Drosophila was first identified as a stimulatory factor in in vitro transcription assays using the engrailed and Ultrabithorax promoters. Subsequent studies have suggested that the GAGA factor promotes transcription by blocking the repressive effects of histones; moreover, it has been shown to function in chromatin remodeling, acting together with other factors in the formation of nuclease hypersensitive sites in vitro. The GAGA factor is encoded by the Trithorax-like locus and in the studies reported here we have used the maternal effect allele Trl13C to examine the functions of the protein during embryogenesis. We find that GAGA is required for the proper expression of a variety of developmental loci that contain GAGA binding sites in their upstream regulatory regions. The observed disruptions in gene expression are consistent with those expected for a factor involved in chromatin remodeling. In addition to facilitating gene expression, the GAGA factor appears to have a more global role in chromosome structure and function. This is suggested by the spectrum of nuclear cleavage cycle defects observed in Trl13C embryos. These defects include asynchrony in the cleavage cycles, failure in chromosome condensation, abnormal chromosome segregation and chromosome fragmentation. These defects are likely to be related to the association of the GAGA protein with heterochromatic satellite sequences which is observed throughout the cell cycle.